PEDAGOGICAL ANALYSIS OF MAHMUDKHOJA BEHBUDI'S WORK "PADERKUSH" - Hilola Lochinbekovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the drama "Padarkush" by Mahmudkhoja Behbudi, one of the major representatives of Jadid literature. The artistic images in it have been interpreted. Compared with our current Eastern customs, the work emphasizes that education plays a major role in ensuring that every person is enlightened and develops into a harmoniously developed individual.